STUDENTS’ PERCEPTIONS OF USING QUIZIZZ IN THE EFL CLASSROOM - Ni Putu Ines Marylena Candra Manik; Putu Wiraningsih; Agus Budiarte; I Kadek Darmo Suputra (Undiksha Press, 2026)
This study investigated students’ perceptions and challenges in using Quizizz as a gamified learning tool in the English as a Foreign Language (EFL) classroom. The rapid integration of digital technologies in education has encouraged teachers to explore interactive platforms that enhance student engagement and motivation. To achieve this purpose, a quantitative descriptive research design was employed involving a group of EFL students who completed a questionnaire adapted from the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The instrument measured four dimensions: performance expectancy, effort expectancy, social influence, and facilitating conditions. The results revealed that students had overall positive perceptions toward the use of Quizizz. The facilitating conditions dimension obtained the highest mean score, indicating that students had adequate facilities and support in using the platform, while social influence scored the lowest, suggesting that intrinsic motivation played a greater role than peer or teacher encouragement. In general, Quizizz was perceived as useful, easy to use, and effective in increasing students’ motivation and participation in learning English. The study recommends that teachers integrate Quizizz as both an assessment and engagement tool to promote more interactive and enjoyable EFL learning experiences.